Penerapan Metode Profile Matching (PM) Dalam Menentukan Pemilihan Duta Generasi Berencana (GenRe) - Atira Nabila; Nelly Astuti Hasibuan; Dito Putro Utomo (Forum Kerjasama Pendidikan Tinggi, 2022)
This study examines the selection of Generation Planning Ambassadors (GenRe) subjectively assessed so that there are several candidates who have the same weighting criteria values, making it difficult for the committee to determine which one is the best. Generation Planning (GenRe) in Pangakalan Koto Baru District by using a decision support system by applying the profile matching method. The final result of the research will be able to simplify the work of the selection process for the Generation Planned Ambassador (GenRe). This method compares the actual data value of a profile to be assessed with the expected profile value, so that the difference in competence (GAP), the smaller (GAP) ) is generated, the greater the value weight, which means it has a greater chance of being recommended for selection. There are 5 (five) criteria used for this calculation, namely Public Speaking, English, Insight, Attitude, and Initiative. The results of this study were carried out by assessing based on ranking using the Profile Matching method, from the 9 (nine) prospective ambassadors there were 2 (two) male ambassador candidates and 7 (Seven) female ambassador candidates. Of the male ambassador candidates, the highest score was Fadlan Ikhsan with a score of 4.48 and the lowest was Rafli Jasna Aziz with a score of 3.48. And for female ambassador candidates with the highest score is Syakina Aulia with a score of 5 and the lowest score is Gisti Rahmatika with a score of 3.5. The results of the ranking of the planned generation of ambassadors are seen from the highest score